Krisis Tiroid dalam Kehamilan - Fadira Rinella Wihandi; Teuku Yudhi Iqbal (Inovasi Kesehatan Global, 2025)
Thyroid crisis is an acute, life-threatening form of thyrotoxicosis and represents one of the severe complications of hyperthyroidism. During pregnancy, thyroid disorders have unique characteristics due to structural and functional changes in the thyroid gland that occur throughout gestation. Pregnancy can influence the course of thyroid disease, and conversely, thyroid disorders may also impact pregnancy outcomes. In this case report, we present a 30-year-old patient, Mrs. F, gravida 5, abortus 4, para 0, who presented with palpitations, fever, restlessness, and a history of uncontrolled hyperthyroidism. The diagnosis of thyroid crisis was made clinically using the Burch & Wartofsky score instrument. Management of thyroid crisis in pregnant women requires a multidisciplinary approach, close monitoring, administration of antithyroid drugs, β-blockers, and other supportive therapies, while also considering fetal safety.